(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the current status of knowledge, attitudes, and practices regarding the prevention of school violence among students of Ca Mau Medical College in 2025, and to identify several related factors. Methods: A descriptive cross-sectional study was conducted among 385 students enrolled at Ca Mau Medical College in 2025 using structured questionnaires administered via interviews and direct observation with monitoring checklists. Results: The proportions of students demonstrating correct knowledge, attitudes, and practices regarding school violence prevention were 64.52%, 62.13%, and 70.25%, respectively. Academic performance, living arrangements, and family economic status were related to knowledge, attitudes, and practices, while gender was related to attitudes and practices toward school violence prevention. Conclusion: The levels of correct knowledge, attitudes, and practices regarding school violence prevention among students at Cà Mau Medical College in 2025 remain limited. Therefore, communication and education activities on school violence prevention should be strengthened continuously through diverse and accessible formats.